Jumonji domain-containing protein RIOX2 is overexpressed and associated with worse survival outcomes in prostate cancers - He, Chenchen; Liu, Wang; Sun, Jiahao; Zhang, Da; Li, Benyi (Frontiers in Oncology, 2023)
Background: Histone demethylase RIOX2 was cloned as a c-Myc downstream gene involved in cell proliferation and has been implicated as an oncogenic factor in multiple tumor types. Its expression profiles and correlation with disease progression in prostate cancers are unknown. Methods: Transcriptomic profiles of Jumanji domain-containing protein genes were assessed using multiple public expression datasets generated from RNA-seq and cDNA microarray assays. RIOX2 protein expression was assessed using an immunohistochemistry approach on a tissue section array from benign and malignant prostate tissues. Gene expression profiles were analyzed using the bioinformatics software R package. Androgen stimulation on RIOX2 protein expression was examined in LNCaP cells by western blot assay. Results: Among 35 Jumanji domain-containing protein genes, 12 genes were significantly upregulated in prostate cancers compared to benign compartments. COX regression analysis identified that the ribosomal oxygenase 2 (RIOX2) gene was the only one significantly associated with disease-specific survival outcomes in prostate cancer patients. RIOX2 upregulation was confirmed at the protein levels using immunohistochemical assays on prostate cancer tissue sections. Meanwhile, RIOX2 upregulation was associated with clinicopathological features, including late-stage diseases, adverse Gleason scores, TP53 gene mutation, and disease-free status. In castration-resistant prostate cancers (CRPC), RIOX2 expression was positively correlated with AR signaling index but negatively correlated with the neuroendocrinal progression index. However, androgen treatment had no significant stimulatory effect on RIOX2 expression, indicating a parallel but not a causative effect of androgen signaling on RIOX2 gene expression. Further analysis discovered that RIOX2 expression was tightly correlated with its promoter hypomethylation and MYC gene expression, consistent with the notion that RIOX2 was a c-Myc target gene. Conclusion: The Jumanji domain-containing protein RIOX2 was significantly overexpressed in prostate cancer, possibly due to c-Myc upregulation. RIOX2 upregulation was identified as an independent prognostic factor for disease-specific survival.